Pengaruh PENGARUH DOSIS BAHAN PENGIKAT TEPUNG UMBI GARUT (Maranta arundinacea) TERHADAP SIFAT FISIK PELET INDIGOFERA (Indigofera zollingeriana): Pellet Indigofera - Jihad, Rohmat Fahrul; Rohayati, MP., Dr. Ir. Tati; Nurhayatin, Titin (JANHUS: Jurnal Ilmu Peternakan Journal of Animal Husbandry Science, 2025)
Abstract The type and dosage of binder affect the quality of the pellets produced. Arrowroot tubers contain starch which has the potential to be used as a binder. This study aims to determine the effect of binder dose of arrowroot tuber flour (Maranta arundinacea) on the physical properties of indigofera pellets (Indigofera zollingeriana). Research on the physical properties of pellets was conducted at the Integrated Laboratory, Faculty of Agriculture, Garut University from July to August 2024. The method used in this research is experimental method. The design used was a completely randomized design (CRD) with 5 treatments and 4 replicates, consisting of P0 (30% Molasses) as control, P1 (20% Arrowroot Flour), P2 (30% Arrowroot Flour), P3 (40% Arrowroot Flour) and P4 (50% Arrowroot Flour). The parameters tested were density, bulk density, compacted density, specific gravity and stack angle. The data obtained were analyzed Using ANOVA and Duncan’s Multiple Range Test at the 5% level. he results showed that the use of different doses of arrowroot tuber flour (Maranta arundinacea) binder affected the physical properties of indigofera (Indigofera zollingeriana) pellets. The use of arrowroot tuber flour with a dose of 40% gave the optimal results on the parameters of pile bulk density, compacted density, and stack angle. Keywords: Binder, Arrowroot Flour, Indigofera, Physical Characteristics, Pellet